The effect of implementation leadership training for nursing informal leaders in the evidence-based practice - Xueyan Huang; Can Wang; Lumeng Lu; Jianao Chen; Rui Wang; Ying Feng; Yuhong Dong; Haifang Zhou (Frontiers in Medicine)
BackgroundImplementation leadership is important for the successful implementation of evidence-based practice (EBP). Informal leaders, who are important promoters of EBP in nursing in the current healthcare system, can affect nursing management, organizational effectiveness, and cultural quality positively. However, informal leaders may lack training in leadership management and EBP. This study evaluated the effectiveness of the training program for implementation leadership, aiming to improve the leadership of informal leaders in EBP.MethodsBased on the Ottawa Model, this study designed a training program for implementation leadership, which lasted for 4 months and had 60 class hours. Seventy-five nursing informal leaders were trained in three steps of “Theoretical Training-Interactive Workshop-Theme Report”. Before the first training and after the last training, we evaluated the training effectiveness using Kirkpatrick’s evaluation model at the four levels of reaction (training satisfaction survey), learning (Evidence-Based Practice Belief Scale), behavior (Evidence-Based Nursing Competence Scale), and result (Implementation Leadership Scale). Data were analyzed by descriptive statistics, and paired t-tests for effect sizes.ResultsAt the reaction level, the informal leaders had 100% engagement and high satisfaction score. At the learning level, the score of the Evidence-Based Practice Belief Scale of informal leaders after training [(69.24 ± 5.32)] vs. [(59.91 ± 5.96)] was significantly higher than that before training (p < 0.001). At the behavior level, the score of the Evidence-Based Nursing Competence Scale of informal leaders after training [(74.47 ± 5.75) vs. [(56.37 ± 7.15)] was significantly higher than that before training (p < 0.001). At the result level, the score of the Implementation Leadership Scale of informal leaders after training [(38.88 ± 2.76) vs. [(30.01 ± 3.24)] was significantly higher than that before training (p < 0.001).ConclusionThe training program is a highly accepted, practical, and effective implementation strategy for informal leaders, which can improve the evidence-based nursing belief, evidence-based nursing competence, and implementation leadership of nursing informal leaders, and has a positive impact on EBP.